Notes to Philosophy 167: Class 5 -- Other Developments in Astronomy from 1609 to 1642 -- Part 6. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Further Telescopic Discoveries: 1610-1620 -- Some Background to Galileo's Dialogue; Generally corresponds to the video segment: Class 5, Part 6.